Physicochemical and sensorial evaluation of biscuit and muffin incorporated with young corn powder - Anis Jauharah, M.Z.; Wan Rosli, W.I.; Robert, S. Daniel (Universiti Kebangsaan Malaysia, 2014)
Various types of natural fibre-rich ingredients are added into bakery-based products to improve their fibre content for health promotional purposes. However, most of these products are frequently added with imported dietary fibre ingredients. The aim of this study was to develop bakery products incorporated with young corn powder (YCP) and to evaluate the effects on physicochemical properties and sensory acceptabilities. Dried young corn was used to substitute wheat flour in biscuit and muffin formulations at different levels (0, 10, 20 and 30%). The effects of YCP incorporation on proximate compositions, physical characteristics, texture profile and sensory evaluation of both bakery products were investigated. The present results showed that YCP had significantly increased protein and total dietary fibre contents of both biscuit and muffin. Hardness attribute of both products increased in line with the level of YCP addition. Interestingly, biscuit and muffin containing 10% YCP received better score than the control and other formulations for most of the sensorial attributes judged. In conclusion, YCP can be potentially be used as an alternative functional ingredient for partial replacement of wheat flour in formulating biscuit and muffin because of its ability to improve the nutritional quality without jeopardizing sensorial palatability.